Combined dipeptidyl peptidase-4 inhibitor with low-dose testosterone exerts greater efficacy than monotherapy on improving brain function in orchiectomized obese rats - Puntarik Keawtep (2019)
© 2019 Elsevier Inc. Both obesity and orchiectomy lead to the development of brain pathologies and cognitive decline. Testosterone replacement therapy (2 mg/kg/day TRT)and dipeptidyl peptidase-4 inhibitor (vildagliptin)improved cognition in orchiectomized rats, and obese rats. However, both had no beneficial effects in brain of orchiectomized-obese rats. TRT (>2 mg/kg/day)is possible to attenuate brain defects in those rats, but high dose of TRT causes adverse effects. Then, combined effect of low-dose TRT (1 mg/kg/day)and vildagliptin on brain and cognitive functions in orchiectomized-obese rats should be investigated. Sixty male rats were fed with either a normal diet (ND)or a high-fat diet (HFD)for 28 weeks. At week 13, both ND and HFD-fed rats had either a sham-operation or an orchiectomy. At week 25, orchiectomized rats were treated with either: a vehicle, 2 mg/kg/day TRT, vildagliptin (3 mg/kg/day)or a combined vildagliptin with 1 mg/kg/day TRT for 4 weeks. Then, metabolic parameters, brain and cognitive functions were determined. Hippocampal oxidative stress, apoptosis, dendritic spine loss, microglial hyperactivity, and cognitive decline were found in orchiectomized ND-fed rats and sham-operated HFD-fed rats. Interestingly, orchiectomy aggravated these brain pathologies and cognitive decline in HFD-fed rats. In orchiectomized ND-fed rats, all treatments restored brain and cognitive functions. In orchiectomized HFD-fed rats, monotherapies ameliorated these brain pathologies, while the combined therapies had the greatest beneficial effect on the brains. These findings suggest the combined therapies may be the best therapeutic approach for restoring brain functions in the orchiectomized-obese condition.